A 4-Year Longitudinal Study of the Sex-Creativity Relationship in Childhood, Adolescence, and Emerging Adulthood: Findings of Mean and Variability Analyses - He, Wu-Jing (Frontiers in Psychology, 2018)
The relationship between sex and creativity remains an unresolved research question. The present study aimed to approach this question through the lens of the developmental theory of sex differences in intelligence, which posits a dynamic pattern of sex differences in intellectual abilities from female superiority in childhood and early adolescence to male superiority starting at 16 years of age. A total of 775 participants from three age groups (i.e., children, adolescents, and emerging adults) completed a four-year longitudinal study comprising four assessments of creative thinking at one-year intervals. Creative thinking was assessed with the Test for Creative Thinking-Drawing Production. While the results revealed female superiority in childhood and early adolescence, male superiority was not found in adolescence and emerging adulthood. Rather, greater sex similarities and greater male variability were found based on mean and variability analyses, respectively. This study elucidated the link between sex and creativity by (1) taking a developmental perspective, (2) employing a 4-year longitudinal design in three age groups (i.e., children, adolescents, and emerging adults), and (3) analyzing sex differences based on both mean and variability analyses.